2017
DOI: 10.1093/ajcp/aqx021
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Significance of Isolated Myeloperoxidase Expression in Pediatric B-Lymphoblastic Leukemia

Abstract: To our knowledge, this is the first report to document the clinical outcomes in a group of pediatric patients with B-ALL that expresses MPO in the absence of other myeloid markers. This group had an increased rate of relapse and a worse event-free survival than the patients with B-ALL who did not express MPO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 18 publications
6
33
0
1
Order By: Relevance
“…The COG MPAL cohort described here, the iBFM AMBI2012 registry study, and the few pediatric case series for MPAL all suggest that beginning with ALL therapy results in similar or greater OS in comparison with AML regimens. A recent meta‐analysis of patients with MPAL also reported a survival benefit from starting with ALL therapy, although patient‐level data revealed equivalent OS with AML therapy .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The COG MPAL cohort described here, the iBFM AMBI2012 registry study, and the few pediatric case series for MPAL all suggest that beginning with ALL therapy results in similar or greater OS in comparison with AML regimens. A recent meta‐analysis of patients with MPAL also reported a survival benefit from starting with ALL therapy, although patient‐level data revealed equivalent OS with AML therapy .…”
Section: Discussionmentioning
confidence: 72%
“…The EGIL system is considered easier to apply in a standardized fashion because the WHO2008 and WHO2016 classifications incorporate the concept of subjective strength of antigen positivity (negative, low, or strong) to delineate lineage specificity . Inherent variability within this approach is evident from the rate of review failure in the COG cohort as well as recent MPAL reports . However, the WHO definition is widely accepted internationally, and its reliance on strongly expressed antigens specific to lineage differentiation is considered most likely to delineate a true MPAL population .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although current WHO guidelines describe MPO expression as a myeloid‐lineage defining feature, the biologic, prognostic, and therapeutic implications of isolated MPO expression (iMPO) in the absence of other myeloid‐defining or myeloid‐associated antigens in blasts that are otherwise immunophenotypically lymphoid have recently become a subject of increased interest. In the context of MPAL B/M, one retrospective series found that B‐ALL with iMPO (defined as B‐ALL expressing MPO but not CD13, CD14, CD33, CD64, or CD117) was associated with a significantly higher incidence of relapse compared with typical B‐ALL, suggesting that iMPO in B‐ALL should be regarded as a high‐risk feature …”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the development of chemoresistance is a key regulator for relapse among children (4,5). Therefore, further understanding of the pathogenesis of B-ALL is of great significance to improve the survival rate of patients (6).…”
Section: Introductionmentioning
confidence: 99%